PENGUATAN GURU DAN ORANG TUA DALAM MENGHADAPI NEW NORMAL DI BIDANG EKONOMI - Made Ayu Anggreni, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The change is dractic felt by the entire population of Indonesia and has not only been damaging in terms of the country's economy, it affects public services, especially in the education sector from Early Childhood Education institutions to higher education levels. Educational institutions located in the orange and red zones, continue Learning from Home, learning from a responsible home of course, the parents or guardians are responsible for guiding their children to keep learning, especially those who need to get parental assistance at the elementary school level and early childhood education units. Parents should be able to replace teacher roles in the new normal. A strong parent figure in this new normal is needed and as a tauladan for his child. Parents who are creative and have new ideas in the field of education or learning at home at the same time can improve the family economy. All educational activities from making herbal drinks for health, producing masks and making Educational Game Tools conducted when the new normal is of great benefit to teachers, parents and early childhood, to add insight into knowledge in the field of economics, skills of parents will be felt and increase income in this difficult situation.